PELUM Association - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
A 'college without walls' is gaining strength in Zimbabwe and in June this year will begin to offer training in sustainable agriculture and community development. This pilot project being established under the auspices of the PELUM (Participatory...